Arsitektur Sistem Informasi Rehabilitasi dan Rekonstruksi Rumah Terkena Dampak Gempa Menggunakan Framework Togaf - Sirajunnasihin Sirajunnasihin; Hendra Setiawan (Jurnal Teknologi Informasi dan Multimedia, 2024)
The study focuses on the impact of the 2018 earthquake in the Province of West Nusa Tenggara, particularly the extensive damage to hundreds of thousands of houses. It aims to assess the initial phase of post-earthquake housing rehabilitation and reconstruction activities and seeks to enhance their efficiency and effectiveness. One of the main issues identified is the absence of an integrated information system to facilitate data management and coordination among relevant agencies, often leading to errors and delays in implementing activities. To address this, the research utilizes the TOGAF ADM Framework as an architectural design method, providing detailed guidelines for creating a flexible and adaptable information system architecture. Data is collected through in-terviews, document studies, and literature reviews. The research delves into the vision and mis-sion, regulations, and guidelines pertaining to the rehabilitation and reconstruction process, as well as an analysis of the current business processes and assets owned by the BPBD of the Province of West Nusa Tenggara. The expected outcome is the development of an information system ar-chitecture that can overcome obstacles in rehabilitation and reconstruction activities, resulting in a more effective and efficient process. Moreover, it aims to enhance coordination and resource uti-lization. Ultimately, the study concludes that implementing a TOGAF ADM-based information system architecture can offer a comprehensive solution to the challenges encountered in post-earthquake housing rehabilitation and reconstruction. This resulting integrated and opti-mized system is expected to serve as a valuable reference for relevant agencies in other provinces facing similar situations in the future.